Formulation of Keruing (Dipterocarpus grandiflorus) Oleoresin Aromatherapy Candles - Butar-Butar, Maria Elvina Tresia; Agus, Adhe Septa Ryant; Leswana, Nurillahi Febria; Fernandes, Andrian (Jurnal Sains dan Kesehatan, 2024)
Aromatherapy is an alternative treatment method that utilizes essential oils and volatile components, such as terpenes and aromatic compounds. The active compounds of keruing oleoresin are phthalic acid, namely phthalic acid di(3-methoxybenzyl) ester and phthalic acid, 5-ethyl-1,3-dioxan-5-yl octyl ester causing keruing oleoresin to have a distinctive fragrance. The purpose of this study was to formulate keruing oleoresin in aromatherapy candle preparations. This research method includes base optimization, formulation of keruing oleoresin aromatherapy candles with concentrations of 0%; 2.5%; 5%; 7.5%; and 10%, and evaluation of aromatherapy candles including organoleptic testing, melting point, and burning time. The results of organoleptic testing of aromatherapy candles in shape, aroma, and color showed that F4 with 10% oleoresin concentration had a more dominant aroma and color. Melting point and burning time tests showed F1 with a concentration of 2.5% had a higher melting point of 54.6°C and a longer burning time of 144 minutes. Keywords:          Dipterocarpus grandiflorus, oleoresin, aromatherapy candle